Enantioselective Synthesis of β‐Nitrophosphonates Using Immobilized Quinine Organocatalyst on Mesoporous SBA‐15 as an Efficient Recyclable Catalyst. Issue 25 (6th July 2018) - Nazish, Mohd; Kumar, Gaurav; Tak, Rajkumar; Khan, Noor‐ul H.; Kureshy, Rukhsana I.
Abstract: Quinine (QN) organocatalyst immobilized on mesoporous SBA‐15 was synthesized by radical polymerization method. The characterization of the synthesized heterogeneous organocatalystQN‐SBA‐15 (4 b ) was accomplished by various physico‐chemical methods to confirm the successful loading of quinine organocatalyst over SBA‐15 material. The heterogeneous organocatalyst4 b was used for asymmetric Michael addition of diphenylphosphite to nitroalkenes. In contrast to its homogeneous analogue, the catalytic activity of4 b was significantly improved as revealed by high enantioselectivity (98%) and yield (92%) of β‐nitro phosphonates when molecular sieve was used as an additive. Moreover, the catalyst was recyclable for five cycles with retention of enantioselectivity and yield. Abstract : Heterogeneous catalyst QN‐SBA‐15 (4 b ) i. e. Quinine (QN) loaded on SBA‐15 was successfully synthesized, characterized and explored for the enantioselective 1, 4 addition of diphenylphosphite to nitroalkenes. The confined medium effect of mesoporous material was observed delivering precursor for β‐amino Phosphonic acid in good yield and good ee up to 98%. The catalyst was recyclable up to five catalytic cycle.